Imunoterapia com Dermatophagoides pteronyssinus associados a extratos bacterianos em pacientes com rinite alérgica: um estudo preliminar - Queirós, Meimei Guimarães Junqueira de (2005)
Background Allergen specific immunotherapy (SIT) is currently the allergy treatment that may lead to modulation of the immune response and reduction of symptoms. Bacterial extracts have been used to prevent or treat allergic diseases, but its clinicai efficacy remains to be determined. Objectives To evaluate clinicai and laboratorial parameters in Brazilian patients with allergic rhinitis/asthma before and after 1 year of SIT, using D. pteronyssinus (Dpt) extract associated or not with bacterial extracts. Patients and Methods One-hundred patients with allergic rhinitis with/without mild asthma were selected for a SIT clinicai trial and distributed into 4 groups: DPT (Dpt extract), MRB (mixed respiratory bacterial extract), DPT+MRB, and Placebo. Clinicai (rhinitis/asthma symptom and medication scores, peak expiratory flow [PEF] measurements, and skin prick test [SPT] to Dpt) and laboratorial (measurements of IgE leveis to Dpt, Der p 1 and Der p 2 allergens) evaluation were performed before and after 1 year of treatment. Results There was a significant reduction of rhinitis symptom/medication scores and increase in PEF values in all groups. The same was observed for asthma symptom/medication scores, except for DPT group. SPT results significantly decreased only in DPT and placebo groups. A significant reduction in mean IgE leveis to Dpt was found in MRB (6.90 vs 5.06) and DPT+MRB (5.53 vs 3.46) groups. Also, only DPT (8.19 vs 6.45) and DPT+MRB (7.53 vs 5.88) groups showed a significant reduction in mean leveis of IgE to Der p 2, but not for Der p 1 allergen. No significant differences were found in intergroup analyses for all clinicai and laboratorial parameters. Conclusion Our results indicate that SIT using Dpt extract associated with bacterial extracts in patients with rhinitis/asthma was useful and effective in the clinicai improvement and in the reduction of specific serum IgE leveis to Dpt and to Der p 2 major allergen just after one year of immunotherapy.